DEDUCTIVE REASONING: THE USE OF THE SELECTION TASK TO MEASURE EDUCATIONAL INTERVENTIONS - Rich Jr., John D (European Scientific Journal, ESJ, 2014)
A common problem with educational interventions is that they require the collection of data across one or many school years before an assessment of their effectiveness can be performed. This paper describes the selection task, and makes the case for its use in evaluating the effectiveness of educational interventions. As an example, a study is described that uses the selection task to determine the degree to which student performance is positively influenced by knowledge of success criteria. Further, this study examined whether the impact of knowledge of this success criteria is inhibited or augmented by the magnitude of the success criteria provided. Participants were given success criteria of 10/10, 8/10, 6/10, 4/10, or nothing (control). Performance on the task was greatest when success criteria were provided, but only when the success criteria were not too strict. Implications for educational practice are discussed.